P-034 Endovascular treatment of dural venous sinus thrombosis. (4th July 2012) - Ho, J; Seinfeld, J; Kumpe, D
Abstract : Introduction: Dural venous sinus thrombosis (DVST) accounts for 0.5% of all strokes. The two largest cohorts report a mortality rate of 8%–13%, 1 2 but mortality rates as high at 30% have been reported. Traditional treatment is systemic anticoagulation. The most recent European Federation of Neurological Societies practice guidelines from 2010 promote intravenous heparin or weight-adjusted subcutaneous low molecular weight heparin as first line treatments, and states that "there is insufficient evidence to support to the use of either systemic or local thrombolysis." We report our single institution experience from 1998 to 2012 of using endovascular local thrombolysis and local rheolytic thrombectomy. Materials and Methods: We performed a retrospective review of 31 consecutive patients who carried a diagnosis of DVST and had an endovascular intervention, including local thrombolysis or rheolytic thrombectomy. The decision to utilize endovascular intervention was based on a combination of severity of clinical symptoms and radiographic evidence of severe thrombus. Results: 31 patients were identified who fit the inclusion criteria, 77% of whom were female. Average age was 35 (range 2–70). Half of the patients had an identified underlying cause. Of the female patients, 33% were taking hormones or were peripartum. An underlying coagulopathy was identified in 20% of patients. Three patients had intracranial tumors resected within days of diagnosis with DVST. Four patients (13%) required decompressive craniectomies due to bleeds or cerebral edema. One patient (3.2%) died. Four patients transferred to outside hospitals and three were lost to follow-up, leaving 24 patients. At discharge, 64% returned to independence (mRS 0–2), and 32% remained dependent (mRS 3–5). Initial follow-up was at 2 months on average, with 79% independent and 21% dependent. At most recent follow-up (mean 48 months, range 1–162 months), 88% were independent and 12% were dependent. These results are comparable to a recent US multicenter cohort study that included patients where 68% were treated with systemic anticoagulation and 15% were treated with endovascular thrombolysis, which showed at discharge, 62% were independent, 28% were dependent, 13% mortality (2). Conclusion: Prompt diagnosis and lysis of clot in DVST is critical. Prolonged venous congestion increases risk of infarction and hemorrhage. The use of endovascular local thrombolytics and rheolytics can drastically decrease the time to recanalization of thrombosed dural venous sinuses with comparable functional outcome and improved mortality. None of the patients in our series have developed a dural arteriovenous fistula. These data suggest that endovascular treatment of patients, with arguably worse clinical status or greater clot burden, using local thrombolytics and/or rheolytic thrombectomy has lower mortality and comparable functional recovery compared to a larger cohort of patients treated primarily with anticoagulatio. 2 Competing interests: None. References: 1. Ferro JM, Canhao P, Stam J, et al. Prognosis of cerebral vein and dural sinus thrombosis: results of the International Study on Cerebral Vein and Dural Sinus Thrombosis (ISCVT). Stroke 2004;35 :664–70. 2. Wasay M, Bakshi R, Bobustuc G, et al. Cerebral venous thrombosis: analysis of a multicenter cohort from the United States. J Stroke Cerebrovasc Dis 2008;17 :49–54.